T2‐weighted prostate MRI at 7 tesla using a simplified external transmit‐receive coil array: Correlation with radical prostatectomy findings in two prostate cancer patients. Issue 1 (20th November 2013) - Rosenkrantz, Andrew B.; Zhang, Bei; Ben‐Eliezer, Noam; Le Nobin, Julien; Melamed, Jonathan; Deng, Fang‐Ming; Taneja, Samir S.; Wiggins, Graham C.
<x xml:space="preserve">Abstract</x> Purpose To report design of a simplified external transmit‐receive coil array for 7 Tesla (T) prostate MRI, including demonstration of the array for tumor localization using T2‐weighted imaging (T2WI) at 7T before prostatectomy. Materials and Methods Following simulations of transmitter designs not requiring parallel transmission or radiofrequency‐shimming, a coil array was constructed using loop elements, with anterior and posterior rows comprising one transmit‐receive element and three receive‐only elements. This coil structure was optimized using a whole‐body phantom. In vivo sequence optimization was performed to optimize achieved flip angle (FA) and signal to noise ratio (SNR) in prostate. The system was evaluated in a healthy volunteer at 3T and 7T. The 7T T2WI was performed in two prostate cancer patients before prostatectomy, and localization of dominant tumors was subjectively compared with histopathological findings. Image quality was compared between 3T and 7T in these patients. Results Simulations of the B1+ field in prostate using two‐loop design showed good magnitude (B1+ of 0.245 A/m/w1/2) and uniformity (nonuniformity [SD/mean] of 10.4%). In the volunteer, 90° FA was achieved in prostate using 225 v 1 ms hard‐pulse (indicating good efficiency), FA maps confirmed good uniformity (14.1% nonuniformity), and SNR maps showed SNR gain of 2.1 at 7T versus 3T. In patients, 7T T2WI showed excellent visual correspondence with prostatectomy findings. 7T images demonstrated higher estimated SNR (eSNR) in benign peripheral zone (PZ) and tumor compared with 3T, but lower eSNR in fat and slight decreases in tumor‐to‐PZ contrast and PZ‐homogeneity. Conclusion We have demonstrated feasibility of a simplified external coil array for high‐resolution T2‐weighted prostate MRI at 7T. J. Magn. Reson. Imaging 2015;41:226–232. © 2013 Wiley Periodicals, Inc.